Not in Their Right Mind? Right-Wing Extremism Is Not a Mental Illness, but Still a Challenge for Psychiatry - Schumann, Frank; Brook, Peter; Heinze, Martin (Frontiers in Sociology, 2022)
Most research in psychiatry on extremism focuses on the question whether there is a connection between extremism and psychiatric diagnoses. In addition, practitioners are increasingly asked to take part in programs aimed at preventing and countering violent extremism by assessing risk for radicalization. However, an issue that remains largely unaddressed is that the rise of the far right in many countries during the last years poses a challenge for psychiatric services as working with right-wing patients can be a source of conflict for practitioners and patients alike. In this article, we assert that the narrow conceptual scope on psychological vulnerabilities and the practical focus on risk assessment contribute to processes of psychiatrization and limit the scope of research on right-wing extremism in psychiatry. By giving a brief overview of social research into right-wing extremism, the article argues that right wing beliefs should not be conceptualized as an expression of psychological vulnerabilities but rather as attempts to deal with conflict-laden social reality. Thus, a shift of perspective in psychiatric research on extremism is needed. On a conceptional level, the scope needs to be broadened to grasp the interplay of individual and social factors in radicalization with sufficient complexity. On a practical level, it is necessary to further investigate challenges for practitioners and institutions working with right-wing extremist patients.